2013
DOI: 10.1007/s13524-013-0231-3
|View full text |Cite
|
Sign up to set email alerts
|

Community-Wide Job Loss and Teenage Fertility: Evidence From North Carolina

Abstract: Using North Carolina data for the period 1990-2010, we estimate the effects of economic downturns on the birthrates of 15-to 19-year-olds, using county-level business closings and layoffs as a plausibly exogenous source of variation in the strength of the local economy. We find little effect of job losses on the white teen birthrate. For black teens, however, job losses to 1 % of the working-age population decrease the birthrate by around 2 %. Birth declines start five months after the job loss and then last f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 36 publications
3
45
0
Order By: Relevance
“…Alternatively, even if contraceptive practices changed relatively little due to the recession, given high levels of economic constraint and uncertainty, more low-SES unmarried women may have opted to terminate their pregnancies. Research has shown some, albeit indirect, evidence of this behavior in a study of women in North Carolina (Ananat et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, even if contraceptive practices changed relatively little due to the recession, given high levels of economic constraint and uncertainty, more low-SES unmarried women may have opted to terminate their pregnancies. Research has shown some, albeit indirect, evidence of this behavior in a study of women in North Carolina (Ananat et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…More likely is that declines in fertility operated through an increased or more effective use of contraceptive technology or an increased use of abortion. Relatively little work has focused on how abortion changed during the recession, although Ananat et al (2013) inferred an increase in abortion from the fact that economic conditions zero to four months after expected conceptions are related to observed teen births in North Carolina. In addition, relatively little work has focused on how the recession might have affected the use of contraceptive technology, although hints of an increase in usage have been found (Finer et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that increases in the percentage of the Iowa population living in poverty were associated with reduced odds of abortion is intriguing. One explanation proposed by Jones and Jerman and others [3,30] is that the economic recession may have increased women's motivation to avoid pregnancy, which in turn would increase their use of contraceptives and/or reduce their sexual activity, thereby contributing to the abortion decline. This hypothesis, however, could also explain a rise in abortions: women who are motivated to prevent pregnancy are also those motivated to seek abortion when faced with an unintended pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Because forced job losses, or job losses not initiated by the worker, are likely not anticipated by workers and communities, they are more likely to reflect exclusively exogenous changes in the economy than the more commonly used unemployment rate, which reflects changes both in the economy and in other phenomena that could independently affect child maltreatment (Ananat, Gassman-Pines, and Gibson-Davis 2011, 2013). Specifically, while the unemployment rate captures exogenous changes in the economy, it also captures the decision of workers to enter or exit the labor force.…”
Section: Methodsmentioning
confidence: 99%